Construção da camada de interface gráfica e de um wizard para o framework GRENJ - Viana, Matheus Carvalho (2009)
Enterprises need information systems for executing their processes on an efficient way. Market demands that these systems are developed at short term, at low cost and they need to get high quality and flexibility. Reuse is a concept of Software Engineering that aims to take this demand into consideration with the reutilization of artefacts, previously built and tested, for developing new systems. Information systems can be developed with reuse-based techniques, such as object-oriented frameworks and application generators. This project presents the process of construction of the graphical user interface layer and an application generator wizard of GRENJ (Business Resource Management implemented in Java, in Portuguese, Gestão de REcursos de Negócios com implementação em Java) framework. In this process, Guiwe (Graphical user interface for web) framework was created to support the building and the instantiation of the graphical user interface layer of GRENJ, which makes use of Java language plus web technologies. The wizard of GRENJ framework was developed with the use of a configurable application generator and the creation of templates and the GRENJ-Gens tool. This tool provides the instantiation of systems on GRENJ framework with the support of different application generators that can utilize the templates of that framework. The graphical user interface and the wizard layers were built on an iterative and intercalated way following the sequence of the patterns of GRN (Business Resource Management, in Portuguese, Gestão de Recursos de Negócios), witch is the pattern language that originated GRENJ framework. Beyond this, the practice of test-driven development was also applied. The advantages of using GRENJ framework with its graphical user interface and its wizard layers were verified with the realization of some case studies.